When the small is beautiful: five years publishing short communications - Fernandes, Daniell R. R. (2024)
Since the publication of the first issue in 2019, Entomological Communications has been publishing original and current short communications of basic and applied research in all areas of Entomology (including acarology and related arthropods). Throughout these years, Entomological Communications published 194 articles in six of its seven different sections (Bioassay, Editorial, Letter, Nomenclatural Act, Protocol & Techniques, Scientific Note, and Viewpoint). As of 2024, we are starting a new era to adapt the journal to Open Science. To this end, we encourage authors to publish in a new section focused on Data Papers.